Comparative complications of prepectoral versus subpectoral breast reconstruction in patients with breast cancer: a meta-analysis - Wu, Yongxiao; Yu, Lizhi; Huang, Miaoyan; Huang, Yanping; Li, Chunyan; Liang, Yiwen; Liang, Weiming; Qin, Tian (Frontiers in Oncology, 2024)
Introduction This meta-analysis aims to evaluate the complications associated with prepectoral breast reconstruction (PBR) compared to subpectoral breast reconstruction (SBR) in patients diagnosed with breast cancer. Materials and methods A comprehensive search was performed in four databases, including Medline, Embase, Web of Science and CENTRAL, to collect literature published up until December 31, 2024. In addition, we conducted a thorough manual examination of the bibliographies of the identified papers, as well as pertinent reviews and meta-analyses. We conducted a search on three clinical trial registries, namely ClinicalTrials.gov, Controlled-trials.com, and Umin.ac.jp/ctr/index.htm. Meta-analyses were conducted on total complications, hematoma, infection, wound healing issues, necrosis, capsular contracture, rippling, animation deformity, and reoperation. Results A total of 40 studies were included in the meta-analysis. Compared with SBR, PBR significantly reduced the incidence of animated malformations (OR=0.37, 95% CI: 0.19 to 0.70, P=0.003, I ²=12%), but increased the incidence of ripples (OR=2.39, 95% CI: 1.53 to 3.72, P=0.0001, I ²=10%) and seroma (OR=1.55, 95% CI: 1.02 to 2.35, P=0.04, increasing I ²=70%). Conclusions Our findings indicate that PBR and SBR have comparable safety profiles, with similar total complication rates. Specifically, PBR is more likely to cause rippling and seroma, whereas SBR is more prone to causing animation deformity. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024565837, identifier CRD42024565837.